Structural and Electrochemical Sodium (De)intercalation Properties of Carbon‐Coated NASICON‐Na3+yV2−yMny(PO4)3 Cathodes for Na‐Ion Batteries. Issue 12 (29th September 2022) - Ghosh, Subham; Barman, Nabadyuti; Patra, Biplab; Senguttuvan, Premkumar
Abstract : Mixed vanadium‐/manganese‐based NASICON cathodes are attractive for practical sodium‐ion battery application due to their low cost and toxicity. Although the previous reports demonstrate remarkable performances of bulk Na3+ y V2− y Mn y (PO4 )3 cathodes, their full utilization is limited by lower electronic conductivities and longer Na‐ion diffusion lengths. To overcome this issue, herein, structural and electrochemical Na (de)intercalation properties of carbon‐coated nanoscale NASICON‐Na3+ y V2− y Mn y (PO4 )3 cathodes are investigated. The Mn‐rich carbon‐coated cathodes display enhanced cycling stabilities (90% retention after 100 cycles) and rate performances (100 mAh g −1 at 5C) compared with their bulk counterparts in low‐voltage window cycling (3.8–2.75 V) due to efficient carbon coating and particle nanosizing. Upon extending the voltage window to 4.2–2.75 V, the Mn‐lean cathodes show better capacity retention (≈100 mAh g −1 for 50 cycles at 1C) whereas the Mn‐rich cathodes undergo structural irreversibility and rapid capacity fading. The in operando X‐ray diffraction and ex situ X‐ray absorption studies shed insights on the structural (ir)reversibility and redox activities of NASICON cathodes upon cycling in different voltage windows. Abstract : Carbon‐coated nanoscale NASICON‐Na3+ y V2− y Mn y (PO4 )3 cathodes through sol–gel‐assisted solid‐state synthesis are tailored. They display enhanced cycling stabilities and rate performances compared with the bulk materials.